Network interactions for pharmaceutical market access: findings from an explorative research. Issue 13 (6th September 2021) - Runfola, Andrea; Guercini, Simone; Milanesi, Matilde
Abstract : Purpose: The purpose of this paper is to investigate pharmaceutical market access (MA) and the interaction between the pharmaceutical company and other business and non-business actors (NBAs) involved in the MA of ethical drugs, to identify the main categories of actors, their role for MA and the content of the interaction, adopting an industrial marketing approach. Design/methodology/approach: A qualitative interpretivist approach is adopted, with interviews as the primary data collection method: 36 interviews have been conducted with 16 key informants from the pharmaceutical industry. Findings: The findings of this study reveal that (i) MA can be seen as a relational-driven activity with specific features owing to the highly regulated nature of the pharmaceutical industry, (ii) there is a multiplicity of business, and NBAs involved in the MA activities with whom pharmaceutical companies interact to acquire knowledge, legitimacy and make MA timely and effective, and (iii) the interaction with each category of actors has specific content. Originality/value: This paper advances the debate on the marketing and management of pharmaceutical companies by emphasizing the importance of MA and the need to conceptualize it according to an industrial marketing perspective, revealing the interdependencies among actors for MA and the content of the interaction. It also contributes to the industrial marketing literature that has recently stressed the importance of NBAs as part of the extended business network of a company by identifying different categories of actors, their role in terms of knowledge and legitimization and the features and the trade-off of the extended business network in highly regulated markets.